Indigo alleviates psoriasis through the AhR/NF-κB signaling pathway: an in vitro and in vivo study - Lin,Yu; Yang,Lihong; Wang,Dongxiang; Lei,Haiqing; Zhang,Yuelin; Sun,Wen; Liu,Jing (PeerJ, 2024)
Background Psoriasis is a chronic inflammatory skin disease. A strong association between the AhR/ NFκB axis and the inflammatory response in psoriasis. Indigo (IDG) has demonstrated significant anti-inflammatory properties. This study aimed to assess the anti-psoriatic efficacy of IDG while investigating the underlying mechanisms involved. Methods In the in vitro experiments, cell viability was assessed using the CCK-8. qRT-PCR was employed to measure the mRNA levels of NF-κB, TNF-α, IL-1β, AhR, and CYP1A1. Western blotting was conducted to examine alterations in cytoplasmic and nuclear AhR protein levels. Additionally, an IDG nanoemulsion (NE) cream was prepared for the in vivo experiments. A psoriasis-like skin lesion mice model was induced using IMQ (62.5 mg/day for 7 days). The severity of psoriasis was evaluated using PASI, and skin lesions were scored while epidermal thickness was assessed via HE staining. The expression of inflammatory markers, including IL-6, IL-13, IL-17A, MCP-1, and TNF-α, was detected in skin lesions using Luminex. The levels of CYP1A1, p65, and p-p65 proteins were determined by Western blotting. Results LPS stimulation significantly elevated TNF-α, IL-6, and NF-κB mRNA levels, which were notably reduced by IDG treatment. Additionally, IDG significantly enhanced the expression of AhR and CYP1A1 mRNA. Further investigation revealed that IDG facilitated AhR translocation from the cytoplasm to the nucleus. In the IMQ-induced psoriasis-like mouse model, IDG NE substantially ameliorated the severity of skin lesions. Moreover, IDG NE treatment reduced the upregulation of inflammatory cytokines such as IL-6, IL-17A, MCP-1, and TNF-α in IMQ-induced skin lesions. It was also observed that IDG NE treatment increased CYP1A1 protein expression while inhibiting p65 and p-p65 protein expression. Conclusion IDG emerges as a promising treatment for psoriasis, demonstrating effective therapeutic outcomes. Its mechanism of action is likely linked to the modulation of the AhR/NFκB signaling pathway.
Keywords: Indigo; Psoriasis; AhR; NF-κB